Legality of Deed of Gift and Sale and Purchase of Sultan Ground Land: Normative Study of Notary Authority in Special Regions - Etty Wahyuningsih (Journal of Legal, Political, and Humanistic Inquiry, 2026)
This study examines the authority of notaries in drafting deeds of gift and sale and purchase related to Sultan Ground land through a normative juridical approach. Sultan Ground land possesses a unique legal status under Indonesian agrarian law, which restricts the transfer of ownership rights. The analysis demonstrates that notaries are not authorized to draft authentic deeds implying the transfer of land rights over Sultan Ground, as such authority lacks a clear statutory basis. Notaries may only document legal acts related to land utilization or occupancy agreements that do not result in the transfer of ownership. Any expansion of notarial authority beyond these limits risks undermining legal certainty and distorting the function of authentic deeds within the legal system. Furthermore, deeds drafted outside the scope of lawful authority may be deemed legally flawed and expose notaries to administrative, civil, and ethical liability. Therefore, a restrictive interpretation of notarial authority is essential to maintain coherence between notarial law and agrarian law, as well as to ensure the validity and legal protection of land-related transactions involving Sultan Ground land.